2004
DOI: 10.2334/josnusd.46.101
|View full text |Cite
|
Sign up to set email alerts
|

Oral colonization of Candida species in perinatally HIV-infected children in northern Thailand

Abstract: Human immunodeficiency virus (HIV) infection remains a serious problem in northern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 16 publications
(17 reference statements)
6
31
3
1
Order By: Relevance
“…A recent study in Poland found approximately 40% of Candida carriage in school children (12 and 18 years of age) in samples collected from the pharynx, supragingival plaque, and carious lesions 25 . A study in northern Thailand also observed a carriage rate of 40% in 15 HIV‐negative children (aged 0.5–7 years) 21 . These prevalence rates are comparable to our data, although the age range of those individuals does not perfectly match those of our study.…”
Section: Discussionsupporting
confidence: 67%
“…A recent study in Poland found approximately 40% of Candida carriage in school children (12 and 18 years of age) in samples collected from the pharynx, supragingival plaque, and carious lesions 25 . A study in northern Thailand also observed a carriage rate of 40% in 15 HIV‐negative children (aged 0.5–7 years) 21 . These prevalence rates are comparable to our data, although the age range of those individuals does not perfectly match those of our study.…”
Section: Discussionsupporting
confidence: 67%
“…Microbiological studies in HIV‐positive children have focused mainly on species of Candida 1,2,12,13,23 . Regarding oral bacteria, Castro et al 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal candidiasis has been demonstrated to be associated with oral yeast colonization and decline in CD4 + cell count 22 . The precise defense mechanisms that limit Candida proliferation are still undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Marked decrease in incidence of oral lesion has been reported in patients receiving highly active antiretroviral therapy (HAART) related to the improvement in immunological function or to inhibition of the fungal secretory aspartyl proteinases (SAPs) that play a pathogenic role in mucosal invasion 1 . Other mechanisms seem to play a fundamental role for the declining rates of OPC 9,22 . It has been suggested that low CD4 + lymphocytes count and high plasma HIV RNA levels significantly correlate with oral Candida carriage, thereby increasing the risk of developing symptomatic infections 21 .…”
Section: Introductionmentioning
confidence: 99%